Royalty Payment Mechanism for Songwriters in Indonesia - Henry Surya Wicaksono; Krisnadi Nasution (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The weak mechanism for royalty payments to songwriters in Indonesia, despite Law No. 28 of 2014 on Copyright clearly regulating moral rights and economic rights. In practice, there are still various violations in the form of unauthorized use of songs, low compliance with royalty payments, and suboptimal performance of Collective Management Organizations (CMOs) and National Collective Management Organizations (NCMOs). This study aims to analyze the concept of songwriters' economic rights, the mechanism for managing royalties, and the effectiveness of legal protection in its implementation. The research method uses a normative juridical approach by examining laws and regulations as well as conceptual data related to copyright management. The results show that although regulations have provided a strong legal basis, the implementation of royalty payment mechanisms still faces structural and technical obstacles, including the transparency of CMOs, the legal awareness of users of works, and weak law enforcement against violations. This study emphasizes the importance of improving the mechanisms for collecting and distributing royalties so that the protection of the economic rights of creators can be carried out effectively and fairly.